PENGARUH IMPLEMENTASI PRINSIP-PRINSIP TATA KELOLA TERHADAP LAPORAN KEUANGAN BUMDES DI KABUPATEN KUANTAN SINGINGI - Nelpion, Piges; Savitri, Enni; Dianto, Volta; Hasan, Mudrika Alamsyah (LPPM Universitas Jambi, 2023)
This study aims to analyze the effect of accountability, transparency, responsibility, professionalism, rule of law on financial statements. The population in this study were 208 BUMDes located in Kuantan Singingi Regency in 2020.Â Respondents are 1) Chairman / Head of BUMDes. 2) Head of finance of BUMDes. 3) Expenditure treasurer. The sample used was 65 BUMDes, namely a total of 195 respondents. The data collection method uses the Proposive Sampling method. The analysis method uses multiple linear regression models. The results of this study indicate that Accountability has a positive effect on BUMDes Financial Reports, the application of bumdes accountability provides financial management that is presented openly, quickly, and precisely. so that the government's goal of reporting good financial report results is achieved. Transparency has a positive effect on BUMDes Financial Statements, being able to provide information that the public needs in a relevant, accurate, timely and reliable manner. Responsibility has a positive effect on BUMDes Financial Statements, a high level of responsiveness from the organization will lead to trust from external parties. Professionalism has a positive effect on BUMDes Financial Statements, the ability of a competent person can really be utilized optimally for the benefit of the organization. The existence of the rule of law can direct government duties and functions in an orderly manner.